Peningkatan Kemampuan Pembuatan Produk Meja Taman Minimalis Melalui Pelatihan Di Bengkel Las Untuk Sma Sunan Bonang Tangerang - I Wayan Sukania; I Wayan Joniarta; Florencia Charlene Teng; Marthinus Chandra (Jurusan Teknik Mesin FT Universitas Mataram, 2026)
Sunan Bonang High School in Tangerang is the partner of PKM this time. The school curriculum does not provide lesson materials on the stages of product design and related studies. This condition results in students' knowledge, understanding, and skills in various aspects related to the design and manufacture of a product being considered lacking. On the other hand, graduates need additional knowledge and skills so that they are better prepared to enter the workforce and are ready to compete in the business world. Initial interviews showed that students were very interested in training activities to improve product design and manufacturing skills. This PKM project focuses on designing and manufacturing an ergonomic minimalist garden table. The materials used are iron Nako and steel plate. Some of the work elements carried out are measuring, cutting, sanding, assembling, welding, grinding, and painting. PKM is carried out in 2 stages. The first stage is an explanation of marketing theory, product design theory, and ergonomic theory, as well as an explanation of product design case studies. Participants learn to design the concept of a garden table with predetermined characteristics. In the second stage, participants practice in groups to realize the product using the equipment available in the welding workshop. Through structured training, it is expected to be able to improve the knowledge, understanding, and skills of training participants. The observation results show that there is a 62% increase in the number of students in understanding the stages of product design and understanding the use of workshop equipment. This indicates that the PKM aimed at SMA Sunan Bonang Tangerang partners has been successful and provided significant benefits